Incentives' Effect in Influenza Vaccination Policy - Yamin, Dan; Gavious, Arieh (Management Science, 2013)
In the majority of developed countries, the level of influenza vaccination coverage in all age groups is suboptimal. Hence, the authorities offer different kinds of incentives for people to become vaccinated such as subsidizing immunization or placing immunization centers in malls to make the process more accessible. We built a theoretical epidemiological game model to find the optimal incentive for vaccination and the corresponding expected level of vaccination coverage. The model was supported by survey data from questionnaires about people's perceptions about influenza and the vaccination against it. Results suggest that the optimal magnitude of the incentives should be greater when less contagious seasonal strains of influenza are involved and greater for the nonelderly population rather than the elderly, and should rise as high as $57 per vaccinated individual so that all children between the ages of six months and four years will be vaccinated. This paper was accepted by Yossi Aviv, operations management.